Ler múltiplas fontes: o desenvolvimento de habilidades para a leitura como processo investigativo - Marcos Celírio dos Santos (2021)
In this study, I set out to investigate what reading skills the students in their final years of elementary school had not yet developed with regard to multiple texts online and to what extent a proposed work with the investigative reading of multiple texts on the internet could contribute to the development of comprehension skills from multiple sources. In order to establish this main research objective, I was inspired by the observations made in relation to the research work that students carried out in the schools in which I have already worked with. In general, the research proposals made by the teachers lacked specific guidelines regarding the search, location and selection of study materials and generated results in which students copied information from a single website and pasted it into a document to be delivered to the teacher. Based on studies on critical reading (DEBOER, 1964; DUKE, PEARSON, 2002; GONÇALVES, 2008; SILVA, 2009, 2011), theories of reading from multiple sources (PERFETTI; ROUET; BRITT, 1999; ROUET, 2006; BRÅTEN; STRØMSØ, 2010; ROUET E BRITT, 2011; DOBLER, 2012; BRITT; ROUET, 2012; ANMARKRUD; BRÅTEN; STRØMSØ, 2014; COSCARELLI; COIRO, 2014; COSCARELLI, 2016; HARTMAN, HARTMAN 1994, 1995; OTERO, 2006; COIRO; DOBLER, PELEKIS, 2019) and the conception of reading from multiple sources as an investigation process that should always start from a question or task, I developed an intervention proposal to be developed with ninth grade students enrolled in a public school in the metropolitan region of Belo Horizonte. The students performed an initial task of searching for information and reading multiple texts on the internet, and then I proposed an intervention project of 11 workshops, totaling thirty lessons of sixty minutes each. During the initial and final tasks, students were instructed to use the verbal protocol technique, and all the work was recorded on video and audio using the aTube Catcher software. The data collection methods of this intervention research, qualitative nature, include audio and video capture with records of the navigation and reading process and the think-aloud verbal protocol, textual productions, developed teaching project and non-participant observation. The data were analyzed in four categories: general analysis of the students' performance in the initial task; presentation and general analysis of each workshop held; general analysis of the students' performance in the final task and, a comparison between the initial and final results. The results indicated that students developed navigation skills linked to digital literacy (NOVAIS; DIAS, 2009). Students also developed skills to: observe the data of the source, analyze the source, evaluate the reliability of the texts, compare information in search of consistency and relevance for the accomplishment of a task, evaluate the sources cited in the texts, evaluate the pertinence of the information, perceive relations of consonance, disagreement or complementarity, synthesize information and integrate information. We also observed that the participants' worldview influenced not only what they read, but also how they read and judged the relevance of the data, what they considered reliable, what they took into account or disregarded and the conclusions they reached.